2022
DOI: 10.1001/jamacardio.2022.2981
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance Imaging Phenotypes and Long-term Outcomes in Patients With Suspected Cardiac Sarcoidosis

Abstract: ImportanceIn patients with sarcoidosis with suspected cardiac involvement, late gadolinium enhancement (LGE) on cardiovascular magnetic resonance imaging (CMR) identifies those with an increased risk of adverse outcomes. However, these outcomes are experienced by only a minority of patients with LGE, and identifying this subgroup may improve treatment and outcomes in these patients.ObjectiveTo assess whether CMR phenotypes based on left ventricular ejection fraction (LVEF) and LGE in patients with suspected ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Second, determining individual patient prognosis and assessment of immunosuppression response in patients with CS using cardiac imaging remains challenging. It has been demonstrated that patients without LGE are at an extremely low risk of arrhythmic events . However, although there is increased risk of arrhythmic events in patients with cardiac involvement identified by LGE, only a fraction of these patients experience arrhythmic events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, determining individual patient prognosis and assessment of immunosuppression response in patients with CS using cardiac imaging remains challenging. It has been demonstrated that patients without LGE are at an extremely low risk of arrhythmic events . However, although there is increased risk of arrhythmic events in patients with cardiac involvement identified by LGE, only a fraction of these patients experience arrhythmic events.…”
Section: Discussionmentioning
confidence: 99%
“…However, although there is increased risk of arrhythmic events in patients with cardiac involvement identified by LGE, only a fraction of these patients experience arrhythmic events. Patients with both RV and LV LGE are at elevated risk of cardiovascular events compared with patients with only LV enhancement . Last, while CS is extremely rare after 70 years of age, as the oldest patient reported in the literature was 80 years old, this patient presented with CS in her 90s, reminding us that CS remains on the differential diagnosis in patients with sustained ventricular arrythmias regardless of age.…”
Section: Discussionmentioning
confidence: 99%
“…Recent CMR data identifying the LGE phenotypes associated with arrhythmic outcomes may help. [10][11][12] Athwal et al demonstrated that LGE phenotypes of CS derived from the pathology and validated by clinical outcomes are associated with worse outcomes but absence of the pathology frequent LGE phenotype was associated with a low risk of arrhythmic events, even in the presence of other (pathology rare)…”
mentioning
confidence: 99%
“…Thus, association of any LGE to the clinical outcomes is CS patients may not be strong. 10 Even though edema imaging on CMR has low sensitivity to detect myocardial inflammation compared with FDG-PET, 13 there are no studies of PET positive, LGE negative histology proven CS. In CMR studies, patients with clinically suspected CS and no LGE have extremely low likelihood of developing ventricular arrythmias sudden cardiac death or heart failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation